Epigenetic Aspects of Engineered Nanomaterials: Is the Collateral Damage Inevitable? - Gedda, Mallikarjuna Rao; Babele, Piyoosh Kumar; Zahra, Kulsoom; Madhukar, Prasoon (Frontiers in Bioengineering and Biotechnology, 2019)
The extensive applications of engineered nanomaterial (ENM) in various fields increases the possibilities of human exposure, thus imposing a huge risk of nanotoxicity. Hence, there is an urgent need for a vigilant risk assessment of these ENMs in response to their toxicological profiling, predominantly in biomedical and biosensor settings. Numerous “toxico-omics” studies have been conducted on ENMs, however, a specific “risk assessment paradigm” dealing with the epigenetic modulations in human owing to the exposure of these modern day toxicants has not been defined yet. This review aims at addressing those critical aspects that are currently preventing the establishment of a suitable risk assessment approach for/against ENM exposure and pointing out those researches, which may be helpful in developing and implementing effective guidance for nano-risk assessment. Literature relating to physicochemical characterization, toxicological behavior of ENMs are analyzed and exposure assessment strategies were explored in order to extrapolate opportunities, challenges and criticisms in the establishment of a baseline for the risk assessment paradigm for the ENMs exposure. Various challenges such as uncertainty in the relation of the physicochemical properties and ENM toxicity, the complexity of the dose-response relationships resulting in difficulty in its extrapolation and measurement of ENM exposure levels emerged as issues in the establishment of traditional risk assessment. Such an appropriate risk assessment approach will provide adequate estimates of ENM exposure risks and will serve as a guideline for appropriate risk communication and management strategies aiming the protection and the safety of the humans.